Characterization of metallothionein protein from hepatopancreas organ of Pilsbryoconcha exilis collected from Cikaniki River, Western Java, Indonesia - SATA YOSHIDA SRIE RAHAYU; WAHYU PRIHATINI (Smujo International, 2020)
Abstract. Rahayu SYS, Prihatini W. 2020. Characterization of metallothionein protein from hepatopancreas organ of Pilsbryoconcha exilis collected from Cikaniki River, Western Java, Indonesia. Nusantara Bioscience 12: 1-5. Freshwater environment, undergoing various changes due to the presence of dangerous toxic anthropogenic waste. It causes pressure on the freshwater biota that lives in it, such as Pilsbryoconcha exilis mussel at the bottom of freshwater. This pressure is controlled by the body through the synthesis of a set of stress proteins. Endogenous proteins, metallothionein (MT), in the body of freshwater biota absorb heavy metals in the body of biota, in the form of stress control. This research identified MT protein on P. exilis from contaminated waters such as the Cikaniki river with the average of mercury levels in water, sediment, and hepatopancreas of mussels using AAS method were 0.001 mg/L, 0.120 mg/L, and 1.318 mg/L respectively. Hepatopancreas of P. exilis was extracted using a Tissue Extraction Reagent I kit (Invitrogen), with procedures following the factory manual. The extract was purified by filtration using Sephadec 50; then, the filtration results were migrated together with the PageRuler TM Unstained Low Range Protein Ladder (Fermentas) in Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis (SDS PAGE) gel medium on Biorad Protein II electrophoresis. After completion of electrophoresis, the gel was stained using Page Blue Protein Staining Solution (Fermentas), following the factory manual procedure. Characterization at this research has succeeded in obtaining the MT-I isoform protein measuring 5, 10, and 25 kDa from the hepatopancreas organ of P. exilis.